Preparation method of porous nickel net electrode material with heterostructure
By generating a nano-nickel zinc alloy layer on the surface layer of the nickel mesh, and forming a nickel/nickel oxide heterostructure through chemical dealloyment and self-limited oxidation reaction, the problem of insufficient catalytic activity of the electrode material is solved, and the efficiency and stability of the electrolytic water hydrogen production reaction is improved.
Patent Information
- Application Number
- CN202510007387.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing alkaline electrolytic hydrogen production technology, the catalytic activity of the electrode material is insufficient, resulting in low hydrogen production efficiency and increasing the production cost of "green hydrogen".
The nano-nickel zinc alloy layer is formed on the nickel mesh surface layer by gas-phase alloying reaction, and a porous nickel mesh electrode material with a nickel/nickel oxide heterostructure is formed through chemical dealloyment and self-limiting oxidation reaction.
The catalytic reaction activity and stability of the electrode material are improved, the contact area with the electrolyte is enhanced, the efficiency of hydrogen production reaction of electrolytic water is promoted, and the production cost is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005227326830000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy, and in particular relates to a method for preparing a porous nickel mesh electrode material with a heterogeneous structure. Background Art
[0002] Renewable energy sources such as wind power and photovoltaics are characterized by volatility and intermittency. The configuration of energy storage systems has become an effective means to solve the problem of large-scale wind and solar power abandonment. Currently, commonly used energy storage technologies include secondary battery technology that stores electrical energy and water electrolysis hydrogen production technology that stores chemical energy. Among them, electrode materials are the key to various energy storage technologies. The performance of electrode materials directly affects the energy conversion efficiency, power output, service life and safety of various energy storage devices. Therefore, the development of efficient and stable electrode materials is an important research direction in the field of energy storage technology.
[0003] As an ideal energy storage medium, hydrogen energy can effectively solve the problem of renewable energy consumption in my country by converting green electricity into green hydrogen through water electrolysis technology. In the industrial field, the "green hydrogen" produced by water electrolysis mainly relies on alkaline water electrolyzers, which have the advantages of maturity, stability and low construction cost. At present, the electrode materials of commercial alkaline electrolyzers are mostly modified by spraying nickel metal on nickel mesh or using nickel mesh foam nickel as the substrate, but their catalytic activity for water electrolysis is insufficient, which limits the hydrogen production efficiency of alkaline electrolyzers. Therefore, in practical applications, the low activity of catalytic electrodes leads to increased electricity costs, which makes the production cost of "green hydrogen" high; in order to effectively reduce the production price of "green hydrogen", it is key to develop high-performance water electrolysis catalytic electrodes to reduce the electricity required for the process of hydrogen production by water electrolysis. Although researchers continue to work hard to improve the activity of transition metal catalysts in the hydrogen evolution reaction, most materials still do not meet the standards for large-scale industrial applications.
[0004] To this end, researchers turned to interface engineering based on nickel mesh, nickel foam or stainless steel mesh, etc., and deposited nanoscale heterostructure interfaces to increase the specific surface area and catalytic activity of electrode materials. However, this solution has the problem of insufficient bonding between the deposited layer and the metal substrate and easy detachment, and the difficulty in constructing the heterostructure interface, which increases the cost of commercial application of electrode materials.
[0005] Therefore, how to choose a suitable preparation method to improve the performance of electrode materials while reducing production costs has become an urgent problem to be solved in the field of alkaline water electrolysis. Summary of the invention
[0006] The present invention aims at the problems in the prior art and discloses a method for preparing a porous nickel mesh electrode material with a heterogeneous structure. The present invention sequentially performs gas phase alloying reaction, chemical dealloying and self-limiting oxidation reaction treatment on the nickel mesh material by using volatile zinc to prepare a porous nickel mesh electrode material with a nickel / nickel oxide heterogeneous structure. The electrode material prepared by the present invention exhibits good hydrogen evolution performance in the process of hydrogen production by electrolysis of water, and has high catalytic reaction activity and excellent stability.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a porous nickel mesh electrode material having a heterogeneous structure; the method comprises the following steps:
[0009] S1: Zinc and nickel mesh (NM) are subjected to a vapor phase alloying reaction to generate a nano nickel-zinc alloy layer on the surface of the nickel mesh; the alloy layer includes Ni 2 Zn 11 Layer, NiZn y Layer; NiZn y The layer is an incompletely alloyed nickel-zinc transition layer; the NiZn y wherein the range of y is selected from Ni:Zn=1:(1-4);
[0010] S2: subjecting the nickel mesh material containing the nano nickel-zinc alloy layer described in S1 to chemical dealloying treatment with an ammonium sulfate solution to obtain a nano nickel mesh material (NM / Ni) having a double continuous porous structure layer on the surface;
[0011] S3: subjecting the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2 to a self-limiting oxidation reaction to obtain a porous nickel mesh electrode material (NM / Ni / NiO) having a nano nickel / nickel oxide heterostructure on the inner surface of the pore structure of the double continuous porous structure layer;
[0012] The surface layer refers to the surface layer of each nickel wire constituting the nickel mesh.
[0013] As a further solution, the mass of zinc in S1 is 10-100 times the mass of nickel mesh.
[0014] As a further embodiment, the NiZn y The range of y is selected from Ni:Zn=1:1.
[0015] As a further solution, the NiZn contained in S1 y Layer thickness and Ni 2 Zn 11 The layer thickness ratio ranges from 1:(5-8).
[0016] As a further solution, the treatment temperature of the gas phase alloying reaction in S1 is selected from 300-700°C; the treatment time is selected from 0.5-4h; and the vacuum pressure is selected from 10-50Pa;
[0017] Furthermore, the processing temperature of the gas phase alloying reaction in S1 is preferably from 450 to 600°C.
[0018] As a further solution, the time of the chemical dealloying treatment in S2 is selected from 8-16 hours, and the temperature is selected from 40-60°C.
[0019] As a further embodiment, the molar concentration of the ammonium sulfate solution in S2 is selected from 0.5-2.5M.
[0020] Furthermore, the molar concentration of the ammonium sulfate solution in S2 is preferably 1M.
[0021] As a further solution, the step of the self-limiting oxidation reaction includes vacuum drying the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2, and then performing low vacuum oxidation.
[0022] Further, the vacuum drying temperature is selected from 20-30°C, and the vacuum drying time is selected from 3-24h;
[0023] Furthermore, the vacuum degree of the low vacuum oxidation is in the range of 1×10 -5 -1×10 3 Pa, the temperature of low vacuum oxidation is selected from 20-30°C, and the time of low vacuum oxidation is selected from 12-48h;
[0024] Furthermore, the vacuum drying time is preferably 3-5 hours;
[0025] Furthermore, the low vacuum oxidation time is preferably from 24 to 36 hours.
[0026] As a further solution, the step S31 is further followed by step S31: exposing the prepared porous nickel mesh electrode material having a nano-nickel / nickel oxide heterostructure to an air environment for 7-30 days for continuous oxidation.
[0027] As a further solution, step S11 is further provided before step S1, and step S11 comprises subjecting the nickel mesh to two sequential pretreatments; the first pretreatment comprises washing the nickel mesh with a solvent; the second pretreatment comprises treating the nickel mesh after the first pretreatment in an acid solution, and then washing and drying the nickel mesh with a pure water solution;
[0028] The step S11 further comprises treating the zinc in an acid solution, and then washing and drying the zinc in a pure water solution.
[0029] Furthermore, in S11, the solvent used in the first pretreatment is selected from one or more solvents of acetone, methanol, ethanol, petroleum ether, ethyl acetate, and ethylene dichloride.
[0030] Furthermore, in S11, the washing treatment includes using ultrasound for treatment; the ultrasound time is selected from 10-30 min; the ultrasound temperature is selected from 20-30° C.; and the number of ultrasound times is selected from 2-5 times.
[0031] Furthermore, in S11, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid; wherein the molar concentration of hydrochloric acid is selected from 2-4M; the concentration of sulfuric acid is selected from 0.1-1M; the concentration of nitric acid is selected from 3-5M; and the molar concentration of acetic acid is selected from 2-5M.
[0032] Furthermore, the drying method is preferably air-drying at room temperature.
[0033] As a further solution, there is a step S21 between S2 and S3; the step S21 includes washing the nano nickel mesh material having a double continuous porous structure layer on the surface prepared in S2 with water and ethanol in sequence.
[0034] The present invention does not limit the specific device for performing the gas phase alloying reaction, and those skilled in the art can select a suitable device for the reaction as needed; the present invention is a preferred example: the device used for the gas phase alloying reaction in S1 includes the following components:
[0035] A heating device, used to provide the temperature required for the gas phase alloying reaction;
[0036] A quartz tube used in conjunction with a heating device, used to contain the nickel mesh and zinc, provide a vapor phase alloying reaction space and maintain a vacuum environment;
[0037] Temperature sensor; the temperature sensor is arranged between the quartz tube and the heating device, and is used to monitor and control the required temperature of the quartz tube;
[0038] A vacuum pump is connected to one side of the quartz tube and is used to maintain a vacuum environment inside the quartz tube;
[0039] A vacuum gauge is connected between the vacuum pump and the quartz tube to monitor and regulate the vacuum pressure required for the quartz tube;
[0040] A graphite boat with a cover, wherein the graphite boat with a cover is a cylindrical structure with a hollow interior, is contained inside a quartz tube, and is used to place a nickel mesh and zinc; the zinc is evenly distributed on the bottom of an inner wall of one side of the graphite boat with a cover;
[0041] A plurality of support members are sequentially arranged in the covered graphite boat along the length direction of the covered graphite boat. The support members are arranged at intervals at the bottom of the inner wall of one side of the covered graphite boat to support the nickel mesh and prevent the nickel mesh from contacting with zinc.
[0042] As a further solution, the device also includes a graphite tube, which is an internal hollow structure and is placed inside the quartz tube. The interior of the graphite tube is used to accommodate a graphite boat with a cover.
[0043] As a further solution, both ends of the graphite tube are provided with detachable graphite plugs for covering the graphite tube.
[0044] As a further solution, the support member is selected from one or more high temperature resistant materials such as ceramic rods and quartz rods.
[0045] As a further solution, the spacing distance of the support members is selected from one half to one quarter of the length of the graphite boat with a cover, so that the interior of the graphite boat with a cover is equally divided and can support the nickel mesh.
[0046] As a further solution, the covered graphite boat is more than 1 meter away from the graphite tube outlet to ensure that the zinc vapor will not diffuse into the quartz tube.
[0047] The characteristics and beneficial effects of the present invention are:
[0048] The present invention uses volatile zinc to prepare a nickel-zinc alloy layer on the surface of the nickel mesh by a vapor phase alloying method; and by adjusting the condition parameters of the vapor phase alloy reaction, NiZn can be successfully obtained in the nickel-zinc alloy layer. y Layer and Ni 2 Zn 11 Layer; NiZn y The layer has the function of stably connecting the inner nickel substrate and can protect the inner nickel substrate material in the subsequent chemical dealloying and self-limiting oxidation reaction. 2 Zn 11 The layer is very brittle and zinc can be easily removed in the subsequent chemical dealloying process to form a uniform bicontinuous porous structure; then, a porous nickel mesh electrode material with a nano-nickel / nickel oxide heterostructure is obtained on the inner surface of the pore structure of the bicontinuous porous structure layer through self-limiting oxidation and continuous oxidation at room temperature; the electrode material obtained by the preparation method has a bicontinuous porous structure, which can accommodate more active sites and promote the rate of hydrogen production reaction by electrolysis of water; the nano-nickel / nickel oxide heterostructure also has a uniform and dense nickel oxide layer, which is beneficial to prevent corrosion of the inner nickel substrate during the hydrogen production reaction by electrolysis of water, thereby improving the stability and durability of the electrode; it has high industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 are the test results of hydrogen evolution experiments in the embodiments of the present invention and the comparative examples, wherein: Figure 1 a is a comparison of the self-limiting oxidation saturated catalyst of samples with different VPA times during the preparation of NM / Ni / NiO electrode and the commercial catalyst of Comparative Example 1; Figure 1 b is the relationship between the current density difference and the scan rate at 0.05 V; Figure 1 c is the Tafel slope; Figure 1 d is the electrochemical impedance diagram; Figure 1 e is the hydrogen evolution stability test of NM / Ni / NiO electrode; Figure 1 f is the hydrogen evolution stability of NM / Ni / NiO electrode at different currents;
[0051] Figure 2 Schematic diagram of preparing a porous nickel mesh electrode material (NM / Ni / NiO) with a heterogeneous structure in an embodiment of the present invention;
[0052] Figure 3 It is the phase analysis of the NM / Ni / NiO electrode provided in the embodiment of the present invention and the comparative example at different times, wherein: Figure 3 a is the XRD pattern of nickel mesh at 500℃ with different vapor phase alloying time and after chemical dealloying; Figure 3 (bd) are SEM images of the nickel mesh after vapor phase alloying at different times; Figure 3 e is the SEM image of the cross section of Ni and Zn vapor phase alloying; Figure 3 f is the stress-strain curve of the nickel mesh and the nickel mesh after vapor phase alloying and chemical dealloying treatment;
[0053] Figure 4 This is the XPS spectrum of the NM / Ni / NiO electrode provided in the embodiment of the present invention, Figure 4 a is the full spectrum; Figure 4 b is Ni 2p; Figure 4 c is Zn 2p; Figure 4 d is O1s;
[0054] Figure 5 : is the microstructure of the NM / Ni / NiO electrode of the embodiment of the present invention and the comparative example; wherein, Figure 5 a is the SEM image of the commercial nickel mesh in Example 1, Figure 5b is a local magnified SEM image of the commercial nickel mesh in Example 1; Figure 5 c is a SEM image of the gas phase alloying cross section of the NM / Ni / NiO electrode prepared in Example; Figure 5 d is the cross-sectional SEM image of the NiZn alloy layer after dealloying;
[0055] Figure 6 It is a schematic structural diagram of a device for preparing a porous nickel mesh electrode material with a heterogeneous structure according to the present invention;
[0056] Figure 7 It is a schematic diagram of part of the internal structure of the device for preparing the porous nickel mesh electrode material with heterogeneous structure of the present invention;
[0057] Figure 8 It is a schematic diagram of the internal structure of a graphite boat with a cover of a device for preparing a porous nickel mesh electrode material with a heterogeneous structure according to the present invention.
[0058] In the present invention, NM represents a nickel mesh material that has not been vapor-phase alloyed; NM / Ni / NiO 15d represents an electrode material oxidized at room temperature for 15 days; NM / Ni / NiO 30d represents an electrode material oxidized at room temperature for 30 days; NM / Ni / NiO 60d represents an electrode material oxidized at room temperature for 60 days; NM / Ni / NiO represents the finally formed porous nickel mesh electrode material with a heterogeneous structure of the present invention.
[0059] Reference numerals:
[0060] 1. Heating device; 2. Quartz tube; 3. Temperature sensor; 4. Vacuum pump; 5. Vacuum gauge; 6. Graphite tube; 7. Graphite boat with cover; 8. Graphite plug; 9. Nickel mesh; 10. Zinc; 11. Support. DETAILED DESCRIPTION
[0061] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.
[0062] At present, the electrode materials of commercial alkaline electrolyzers are mostly modified by spraying nickel metal on nickel mesh or using nickel mesh foam nickel as the substrate, but their catalytic activity in water electrolysis is insufficient, which limits the hydrogen production efficiency of alkaline electrolyzers. Therefore, in practical applications, the low activity of catalytic electrodes leads to increased electricity costs, which makes the production cost of "green hydrogen" high; in order to effectively reduce the production price of "green hydrogen", it is key to develop high-performance water electrolysis catalytic electrodes to reduce the electricity required for the water electrolysis hydrogen production process. Although researchers continue to work hard to improve the activity of transition metal catalysts in the hydrogen evolution reaction, most materials still do not meet the standards for large-scale industrial applications.
[0063] Therefore, optimizing a new process to prepare high-performance, low-cost and stable water electrolysis catalytic electrode materials is the current research focus of this application.
[0064] In a first aspect, the present invention provides a method for preparing a porous nickel mesh electrode material having a heterogeneous structure; the method comprises the following steps:
[0065] S1: Zinc and nickel mesh (NM) are subjected to a vapor phase alloying reaction to generate a nano nickel-zinc alloy layer on the surface of the nickel mesh; the alloy layer includes Ni 2 Zn 11 Layer, NiZn y Layer; NiZn y The layer is an incompletely alloyed nickel-zinc transition layer; the NiZn y wherein the range of y is selected from Ni:Zn=1:(1-4);
[0066] S2: subjecting the nickel mesh material containing the nano nickel-zinc alloy layer described in S1 to chemical dealloying treatment with an ammonium sulfate solution to obtain a nano nickel mesh material (NM / Ni) having a double continuous porous structure layer on the surface;
[0067] S3: subjecting the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2 to a self-limiting oxidation reaction to obtain a porous nickel mesh electrode material (NM / Ni / NiO) having a nano nickel / nickel oxide heterostructure on the inner surface of the pore structure of the double continuous porous structure layer;
[0068] The surface layer refers to the surface layer of each nickel wire constituting the nickel mesh.
[0069] The present invention utilizes the volatility of zinc (abbreviated as Zn) and prepares a uniformly deposited Ni layer on the surface of the nickel mesh by performing a vapor phase alloying reaction on the nickel mesh. 2 Zn 11 and NiZn y The nickel-zinc alloy layer is then chemically dealloyed to 2 Zn 11 The zinc layer is etched to form a nano nickel mesh material with a double continuous porous structure layer on the surface; at the same time, it also has a stable NiZn y transition layer; finally, a more uniform, dense and stable nickel oxide layer is formed on the inner surface of the pore structure of the double continuous porous structure layer through a self-limiting oxidation reaction; a porous nickel mesh electrode material with a nano-nickel / nickel oxide heterostructure is obtained.
[0070] The Ni-Zn alloy layer can be obtained from the surface to the inside by adjusting the feed ratio of zinc in the gas phase alloy and the gas phase alloying reaction parameters. 2 Zn 11 Layer, NiZn yLayer; Ni 2 Zn 11 The layer is brittle and evenly distributed, which is conducive to effective removal in the subsequent chemical dealloying process and forms a uniform bicontinuous porous structure layer. y The layer serves as a transition layer, connecting the double continuous porous structure layer and the inner nickel substrate; it has good connection strength.
[0071] The introduction of the nickel oxide layer obtained by the self-limiting oxidation reaction on the inner surface of the pore structure of the bicontinuous porous structure layer is conducive to improving the corrosion resistance of the electrode and extending the service life of the electrode. The prepared porous nickel mesh electrode material with heterogeneous structure shows good catalytic activity and stability in the process of hydrogen production by electrolysis of water; the increase in the number of active sites is conducive to improving the contact efficiency between the reactants and the porous nickel mesh electrode material, enhancing the conduction rate of the active substances, thereby further improving the efficiency of hydrogen production by electrolysis of water.
[0072] Furthermore, the porous nickel mesh electrode material with a heterogeneous structure obtained by the present invention first has a main porous skeleton constructed by nickel wires in the nickel mesh, and further has a porous skeleton composed of Ni on the surface of each nickel wire. 2 Zn 11 The double continuous porous structure layer is formed by dealloying, and there is NiZn between the double continuous porous structure layer and the inner nickel substrate. y The layer serves as a transition layer. In addition, in the bicontinuous porous structure layer, the inner surface of the pore structure of the bicontinuous porous structure layer has a nano nickel / nickel oxide heterostructure (Ni / NiO) formed by a self-limiting oxidation reaction. This structural design not only increases the active sites on the surface of the nickel mesh, increases the contact area with the electrolyte and active substances, and promotes the efficiency of hydrogen production by electrolysis of water; it also helps to maintain the mechanical strength of the nickel mesh itself, which is beneficial to improving the structural stability and recycling performance of the electrode material.
[0073] The material has a double continuous porous structure, which means that on the surface of each nickel wire, Ni 2 Zn 11 The pores of the porous nickel layer formed after dealloying and the ligaments that construct the pores (i.e., the Ni remaining after dealloying) are continuous with each other; this structure of dual-continuous existence of ligaments and pores can improve the mass transfer efficiency; the large specific surface area provides abundant active sites for the catalytic reaction; and it has high catalytic activity.
[0074] As a further solution, the mass of zinc in S1 is 10-100 times the mass of nickel mesh.
[0075] As a further embodiment, the NiZn yThe range of y is selected from Ni: Zn = 1: 1. The NiZn layer within this preferred range has high stability and good mechanical properties, which helps to maintain the structural integrity of the nickel mesh during the subsequent chemical dealloying process, and prevents corrosion of the inner nickel substrate material during the self-limiting oxidation reaction, which can effectively prevent the nickel mesh from breaking or deforming during the treatment process, better bond with the inner nickel substrate, and further improve the catalytic activity and corrosion resistance of the electrode material.
[0076] As a further solution, the NiZn contained in S1 y Layer thickness and Ni 2 Zn 11 The layer thickness ratio ranges from 1:(5-8).
[0077] As a further solution, the treatment temperature of the gas phase alloying reaction in S1 is selected from 300-700°C; the treatment time is selected from 0.5-4h; the vacuum pressure is selected from 10-50Pa; and suitable alloying reaction conditions promote the NiZn y Layer and Ni 2 Zn 11 The effective formation and thickness control of the layer. By selecting the appropriate vapor phase alloying treatment temperature, it is beneficial to promote the uniform volatilization and deposition of zinc and provide suitable alloying reaction energy, thereby ensuring the formation of Ni 2 Zn 11 Layer with NiZn y The uniformity and density of the layer.
[0078] When the selected vapor phase alloying temperature is too low or the time is too short, the volatilization rate of zinc will be slow, making it difficult to achieve uniform deposition, which is not conducive to the formation of stable NiZn y layer as a transition layer; at the same time, its surface is not enough to form a Ni 2 Zn 11 layer; affects the efficiency of chemical dealloying reaction; is not conducive to the formation of a double continuous porous structure on the surface; and when the temperature is too high or the time is too long, it may cause thermal damage to the nickel mesh material, or cause excessive growth of the alloy layer, destroying the inner nickel base material; affecting the mechanical properties and structural stability of the nickel mesh material.
[0079] The selection range of vacuum pressure is also relatively important, in order to ensure that zinc can volatilize and deposit in a relatively stable environment during the vapor phase alloying process. When the vacuum degree is too low, that is, when the pressure is too high, it will increase the collision between gas molecules and affect the uniform volatilization of zinc; when the vacuum degree is too high, that is, when the pressure is too low, although it can reduce the collision between gas molecules, it will increase the operating cost of the equipment and may affect the deposition efficiency of zinc. Therefore, choosing an appropriate vacuum pressure range can ensure the uniform volatilization and deposition of zinc, thereby obtaining a stable NiZny layer and uniformly distributed Ni 2 Zn 11 layer; it is conducive to obtaining a uniform and stable bicontinuous porous structure through subsequent chemical dealloying technology.
[0080] Furthermore, the processing temperature of the gas phase alloying reaction in S1 is preferably from 450 to 600°C.
[0081] As a further solution, the time of the chemical dealloying treatment in S2 is selected from 8-16 hours, and the temperature is selected from 40-60°C.
[0082] As a further embodiment, the molar concentration of the ammonium sulfate solution in S2 is selected from 0.5-2.5M.
[0083] When the time, temperature and molar concentration of the chemical dealloying solution are within the control range of the present invention, it is beneficial to achieve the nickel removal on the basis of maintaining the integrity of the porous structure of the nano nickel mesh material. 2 Zn 11 When the chemical dealloying reaction time is too short or the temperature and molar concentration are too low, the zinc may not be fully etched, resulting in incomplete formation of the porous structure or inappropriate pore size, which affects the penetration and diffusion of the electrolyte, reduces the number of active sites for the catalytic reaction during the electrolysis of water to produce hydrogen, and thus affects the catalytic performance of the electrode material. When the chemical dealloying reaction time is too long or the temperature and molar concentration are too high, it may cause excessive corrosion of the nickel mesh material, destroying the bicontinuous porous structure and the NiZn y The structural integrity of the outer and inner nickel substrates affects the mechanical properties and stability of the electrode materials during the process of hydrogen production by electrolysis of water, resulting in waste of resources and increased costs.
[0084] Furthermore, the molar concentration of the ammonium sulfate solution in S2 is preferably 1M.
[0085] As a further solution, the step of the self-limiting oxidation reaction includes vacuum drying the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2, and then performing low vacuum oxidation.
[0086] Further, the vacuum drying temperature is selected from 20-30°C, and the vacuum drying time is selected from 3-24h;
[0087] Furthermore, the vacuum degree of the low vacuum oxidation is in the range of 1×10 -5 -1×10 3 Pa, the temperature of low vacuum oxidation is selected from 20-30°C, and the time of low vacuum oxidation is selected from 12-48h;
[0088] Furthermore, the vacuum drying time is preferably 3-5 hours;
[0089] Furthermore, the low vacuum oxidation time is preferably from 24 to 36 hours.
[0090] By optimizing the time and temperature of the self-limiting oxidation reaction, it is beneficial to have a uniform and dense nickel oxide layer in the nano nickel / nickel oxide heterostructure formed on the inner surface of the pore structure of the double continuous porous structure layer, avoiding the uneven growth of the nickel oxide layer and excessive oxidation that damages the inner nickel base material due to inappropriate temperature and time; obtaining a suitable nickel oxide layer thickness by regulation is helpful for the penetration of the electrolyte and the precipitation of the gas, further improving the efficiency of hydrogen production by electrolysis of water.
[0091] As a further solution, the step S31 is further followed by step S31: exposing the prepared porous nickel mesh electrode material having a nano-nickel / nickel oxide heterostructure to an air environment for 7-30 days for continuous oxidation.
[0092] The design of this step is conducive to further enhancing the stability and uniformity of the oxide layer within the nano-nickel / nickel oxide heterostructure on the surface of the porous nickel mesh electrode material: through long-term air exposure, the oxide layer has the opportunity to further stabilize and homogenize; this helps to reduce the performance fluctuations of the porous nickel mesh electrode material during the hydrogen evolution reaction, and can more effectively promote the hydrogen ion reduction reaction during the water electrolysis process, thereby improving the hydrogen production efficiency. In addition, a more stable and dense oxide layer can protect the porous nickel mesh electrode material from corrosion by the electrolyte during the hydrogen evolution reaction and extend the service life of the electrode; at the same time, it can also reduce the shedding of active substances and maintain the integrity of the electrode structure, thereby improving the stability and continuity of the electrolysis process. Improve corrosion resistance: The nickel oxide layer generally has better corrosion resistance than pure nickel. Through continuous oxidation, the thickness and density of the nickel oxide layer can be further increased, thereby improving the corrosion resistance of the entire electrode material and extending its service life.
[0093] As a further solution, step S11 is further provided before step S1, and step S11 comprises subjecting the nickel mesh to two sequential pretreatments; the first pretreatment comprises washing the nickel mesh with a solvent; the second pretreatment comprises treating the nickel mesh after the first pretreatment in an acid solution, and then washing and drying the nickel mesh with a pure water solution;
[0094] The step S11 further comprises treating the zinc in an acid solution, and then washing and drying the zinc in a pure water solution.
[0095] Furthermore, in S11, the solvent used in the first pretreatment is selected from one or more solvents of acetone, methanol, ethanol, petroleum ether, ethyl acetate, and ethylene dichloride.
[0096] Furthermore, in S11, the washing treatment includes using ultrasound for treatment; the ultrasound time is selected from 10-30 min; the ultrasound temperature is selected from 20-30° C.; and the number of ultrasound times is selected from 2-5 times.
[0097] Furthermore, in S11, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid; wherein the molar concentration of hydrochloric acid is selected from 2-4M; the concentration of sulfuric acid is selected from 0.1-1M; the concentration of nitric acid is selected from 3-5M; and the molar concentration of acetic acid is selected from 2-5M.
[0098] Furthermore, the drying method is preferably air-drying at room temperature.
[0099] By subjecting zinc and nickel meshes to appropriate solvent treatment or soaking in acidic solutions, it is helpful to fully improve their surface activity and cleanliness. This treatment method can effectively remove surface impurities and oxide layers, making the surfaces of zinc and nickel meshes smoother and purer. In this way, it is not only conducive to the subsequent vapor phase alloying of zinc and enhancing the bonding force between zinc and nickel mesh, but also improves the conductivity and corrosion resistance of the overall nickel mesh material; it is conducive to achieving a more efficient water electrolysis hydrogen production reaction when the nickel mesh is used as a catalytic electrode for hydrogen evolution reaction; it improves the catalytic efficiency, thereby showing better performance in processes such as water electrolysis hydrogen production.
[0100] As a further solution, there is a step S21 between S2 and S3; the step S21 includes washing the nano nickel mesh material having a double continuous porous structure layer on the surface prepared by S2 with water and ethanol in sequence. This step is conducive to the subsequent self-limiting oxidation reaction, improves the purity and stability of the nano nickel mesh material, removes impurities and by-products remaining on the surface, and ensures that it can participate in the subsequent self-limiting oxidation reaction more effectively.
[0101] The present invention does not limit the specific device for performing the gas phase alloying reaction, and those skilled in the art can select a suitable device for the reaction as needed; the present invention is a preferred example: the device used for the gas phase alloying reaction in S1 includes the following components:
[0102] A heating device 1, used to provide the temperature required for the gas phase alloying reaction;
[0103] The quartz tube 2 used in conjunction with the heating device 1 is used to accommodate the nickel mesh 9 and the zinc 10, provide a gas phase alloying reaction space and maintain a vacuum environment;
[0104] Temperature sensor 3; the temperature sensor 3 is arranged between the quartz tube 2 and the heating device 1, and is used to monitor and control the required temperature of the quartz tube 2;
[0105] A vacuum pump 4 is connected to one side of the quartz tube 2 and is used to maintain a vacuum environment inside the quartz tube 2;
[0106] A vacuum gauge 5 is connected between the vacuum pump 4 and the quartz tube 2 and is used to monitor and regulate the vacuum pressure required by the quartz tube 2;
[0107] A graphite boat 7 with a cover, wherein the graphite boat 7 with a cover is a cylindrical structure with a hollow interior, and is accommodated in the quartz tube 2, and is used to place a nickel mesh 9 and zinc 10; the zinc 10 is evenly distributed on the bottom of the inner wall of one side of the graphite boat 7 with a cover;
[0108] Several support members 11 are sequentially arranged in the covered graphite boat 7 along the length direction of the covered graphite boat 7 . The support members 11 are spaced apart at the bottom of the inner wall of one side of the covered graphite boat 7 to support the nickel mesh 9 and prevent the nickel mesh 9 from contacting the zinc 10 .
[0109] The device provided by the present invention not only has the advantages of easy operation and simple process when performing a vapor phase alloying reaction on the nickel mesh 9 to prepare a nickel-zinc alloy, but also can timely regulate the progress of the vapor phase alloying reaction by monitoring the temperature and vacuum pressure, which is beneficial to obtaining a porous nickel mesh electrode material with a suitable nickel oxide thickness layer; in addition, when the device of the present invention performs vapor phase alloying, compared with traditional devices, the device of the present invention places the reaction sample inside the covered graphite boat 7, which is beneficial to improving the uniformity and efficiency of the vapor phase alloying reaction.
[0110] The use of the covered graphite boat 7 can ensure that the sample is heated evenly during the reaction process, reducing the problem of incomplete reaction caused by local overheating or uneven temperature. At the same time, the covered graphite boat 7 has good thermal stability and can withstand high temperature environments, which is very beneficial for the gas phase alloying reaction, effectively protecting the stability and service life of the quartz tube 2, and is suitable for large-scale continuous production applications.
[0111] In addition, the device of the present invention also provides a support member 11 inside the covered graphite boat 7 to separate the nickel mesh 9 and the zinc 10, which is beneficial to form a uniform nickel-zinc layer during the gas phase alloying reaction; avoids the contact between the zinc 10 and the nickel mesh 9, which leads to uneven penetration during the gas phase alloying reaction; prevents excessive local embedding of zinc 10, which causes a decrease in the mechanical strength of the porous nickel mesh electrode material with a heterogeneous structure and destroys its structure; thereby reducing the service life of the electrode during the electrolysis of water to produce hydrogen.
[0112] As a further solution, the device also includes a graphite tube 6, which is an internal hollow structure and is placed inside the quartz tube 2. The inside of the graphite tube 6 is used to accommodate a covered graphite boat 7; placing the covered graphite boat 7 inside the graphite tube 6 and performing a heating reaction inside the quartz tube 2 is beneficial to improving the heating efficiency and facilitating temperature control. Due to its good thermal conductivity, the graphite tube 6 can quickly and evenly transfer heat to the covered graphite boat 7 and the sample inside it. In addition, the use of the graphite tube 6 can also reduce thermal radiation losses, because graphite has a high emissivity, which helps to maintain a high temperature environment in the reaction area. Using the graphite tube 6 inside the quartz tube 2 can also play a protective role, preventing the covered graphite boat 7 from directly contacting the quartz tube wall, avoiding possible contamination or reaction; and can also enhance the stability and durability of the device.
[0113] As a further solution, removable graphite plugs 8 are provided at both ends of the graphite tube 6 for covering the graphite tube 6 .
[0114] As a further solution, the support member 11 is selected from one or more high temperature resistant materials such as ceramic rods and quartz rods.
[0115] As a further solution, the spacing distance of the support members 11 is selected from one half to one quarter of the length of the graphite boat with cover, so that the inside of the graphite boat with cover 7 is equally divided and can support the nickel mesh 9 .
[0116] As a further solution, the covered graphite boat 7 is more than 1 meter away from the outlet of the graphite tube 6 to ensure that the zinc vapor will not diffuse into the quartz tube.
[0117] In a second aspect, the present invention provides a porous nickel mesh electrode material with a heterogeneous structure, wherein the porous nickel mesh electrode material has a main porous skeleton constructed by nickel wires in the nickel mesh, and on the surface of each nickel wire, there is a double continuous porous structure layer formed by a nickel material, and between the double continuous porous structure layer and the inner nickel substrate, there is also a NiZn y The layer is used as a transition layer. In the bicontinuous porous structure layer, the inner surface of the pore structure of the bicontinuous porous structure layer has a nano-nickel / nickel oxide heterogeneous structure formed by a self-limiting oxidation reaction; wherein NiZn y The range of y is selected from Ni:Zn=1:(1-4).
[0118] As a further solution, in the nano nickel / nickel oxide heterostructure of the porous nickel mesh electrode material with heterostructure, the thickness of the nickel oxide layer is 1-10 nm.
[0119] In the present invention, in the nano nickel / nickel oxide heterostructure of the porous nickel mesh electrode material with a heterostructure, the nickel oxide layer thickness of 1-10 nm refers to the thickness of the nickel oxide layer in the nano nickel / nickel oxide heterostructure generated by a self-limiting oxidation reaction on the inner surface of the pore structure of the double continuous porous structure layer of the nickel wire.
[0120] As a further solution, the bicontinuous porous structure layer thickness of the porous nickel mesh electrode material with heterogeneous structure is 9-20 μm.
[0121] As a further solution, the porous nickel mesh electrode material with heterogeneous structure has primary pores and secondary pores; the primary pores have a pore diameter of 5-10 nm; and the secondary pores have a pore diameter of 1-100 μm.
[0122] In the present invention, the primary pores refer to the primary pore structure in the double continuous porous structure layer formed by the nickel material on the surface of each nickel wire; the secondary pores refer to the secondary pore structure of the main porous skeleton constructed by the nickel wires in the nickel mesh.
[0123] As a further solution, the thickness of the inner nickel substrate of the porous nickel mesh electrode material with a heterogeneous structure ranges from 30 to 250 μm.
[0124] As a further solution, the thickness of the inner nickel substrate of the porous nickel mesh electrode material with a heterogeneous structure is preferably in the range of 60-100 μm.
[0125] As a further solution, the double continuous porous structure layer of the porous nickel mesh electrode material with heterogeneous structure and NiZn y The total layer thickness ranged from 15-80 μm.
[0126] As a further solution, in the porous nickel mesh electrode material with heterogeneous structure, the bicontinuous porous structure layer and the NiZn y The ratio of the total thickness of the layer to the thickness of the inner nickel substrate is selected from the range of 1:(2-5).
[0127] As a further solution, the porous nickel mesh electrode material with a heterogeneous structure satisfies at least one of the following conditions or preferably all of the following conditions: a current density of 100 mA cm -2 The overpotential η is 100-150mV and the current density is 800mAcm -2 The overpotential η is 200-300mV, the electrochemical impedance is 4-7Ω at 100mV, and the fracture strength is 60-90MPa.
[0128] The present invention successfully prepares a porous nickel mesh electrode material with a heterogeneous structure by performing vapor phase alloying and dealloying of zinc on a nickel mesh; the electrode material has a bicontinuous porous structure, which is beneficial to increase the contact area with the electrolyte, thereby increasing the number of active sites for the catalytic reaction and accelerating the efficiency of hydrogen production by electrolysis of water; at the same time, the nanoscale porous structure is also beneficial to the rapid transfer and dispersion of heat, avoiding the occurrence of local overheating, thereby improving the stability and safety of the water electrolysis process. At the same time, the structure also has a stable NiZn y The layer serves as a transition layer, connecting the double continuous porous structure layer and the inner nickel substrate; it is beneficial to the long-term stability and durability of the electrode material.
[0129] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0130] Example 1
[0131] 1. Preparation of Nano-Ni-Zn Alloy Layer
[0132] Pre-treated nickel mesh:
[0133] At 20-30°C, ultrasonically clean a 100-mesh nickel mesh in acetone for 10 minutes. Repeat this step three times after replacing the acetone to remove surface grease.
[0134] Next, the nickel mesh was ultrasonically cleaned in ethanol for 10 min, and this step was repeated three times after replacing the ethanol;
[0135] The Ni mesh was placed in 3M HCl, ultrasonicated for 10 min, washed with ultrapure water, and air-dried at room temperature.
[0136] Pretreatment of zinc particles:
[0137] The zinc particles were placed in 0.1 MH 2 SO 4 Ultrasonic cleaning was performed for 10 min, and the samples were cleaned with ultrapure water and air-dried at room temperature.
[0138] Gas phase alloying reaction:
[0139] The cylindrical graphite boat 7 with a hollow interior is opened, and about 5g of pretreated Zn particles are evenly placed in the bottom of the inner wall of the graphite boat 7 with a cover, and about 1cm×1cm of pretreated Ni mesh (0.05g) is placed in the graphite boat 7 with a cover, and it is placed on the support 11 in the graphite boat 7 with a cover, ensuring that the Zn particles and the Ni mesh are not in direct contact, and the graphite boat 7 with a cover is closed; the graphite boat 7 with a cover is placed in the graphite tube 6, and then the two ends of the graphite tube 6 are placed in the graphite plug 8 to cover; the covered graphite tube 6 is placed in the quartz tube 2, and before sealing the tube, the quartz tube 2 is cleaned three times by vacuuming-filling argon gas to exhaust the air in the tube. After the quartz tube 2 is sealed under vacuum conditions, the vacuum pressure is adjusted to 40Pa; the quartz tube 2 is placed in the heating device 1, first heated from room temperature to 500℃ for 25 minutes, and then kept at 500℃ for 30 minutes, and cooled naturally after the insulation is completed. A nickel-zinc alloy layer is formed on the surface of the nickel mesh by a vapor phase alloying reaction. At this time, the main components of the nickel mesh are Ni 2 Zn 11 layer, NiZn layer, Ni layer.
[0140] 2. Preparation of porous nickel mesh electrode materials with heterogeneous structures
[0141] Chemical dealloying treatment:
[0142] The prepared nickel mesh material containing the nano nickel-zinc alloy layer was placed in a 1M ammonium sulfate solution and subjected to chemical dealloying treatment at 50°C for 8 hours. After the treatment, it was washed with water and ethanol three times respectively to obtain a nano nickel mesh material with a double continuous porous structure layer on the surface. At this time, the primary pore diameter of the nano nickel mesh material is 5-10nm.
[0143] Self-limiting oxidation reaction:
[0144] The newly prepared nanoporous nickel was placed in a plastic vacuum desiccator at 20-30°C and vacuumed for 3 hours; a certain amount of air was introduced to make the air pressure reach 900Pa.
[0145] In a thin air environment, the sample was kept at room temperature for 24 hours to obtain a porous nickel mesh electrode material with a heterogeneous structure.
[0146] The electrode material was exposed to ambient air for 30 days for continuous surface oxidation, thereby obtaining a more stable porous nickel mesh electrode material with a heterogeneous structure.
[0147] Example 2
[0148] The specific steps and methods are the same as those in Example 1, except that the vapor phase alloying reaction is carried out at 500° C. for 60 minutes.
[0149] Example 3
[0150] The specific steps and methods are the same as those in Example 1, except that the reaction time of the chemical dealloying reaction is selected from 8 hours and the temperature is selected from 40°C.
[0151] Example 4
[0152] The specific steps and methods are the same as those in Example 1, except that the vacuum drying temperature of the self-limiting oxidation reaction is selected from 25° C. and the time is selected from 8 h.
[0153] Example 5
[0154] The specific steps and methods are the same as those in Example 1, except that the low vacuum oxidation temperature of the self-limiting oxidation reaction is selected from 25° C., the time is selected from 20 h, and the gas pressure is selected from 500 Pa.
[0155] Comparative Example 1
[0156] A commercial nickel mesh electrode (Shanghai Juna New Materials Technology Co., Ltd., ligament 0.065 mm, pore size 0.23 mm, thickness 0.8 mm) was used to directly perform the water electrolysis performance test.
[0157] Comparative Example 2
[0158] The specific steps and methods are the same as those in Example 1, except that the nickel mesh in Example 1 is not subjected to vapor phase alloying, chemical dealloying, and self-limiting oxidation reaction, and the electrolysis water performance test is directly performed.
[0159] Comparative Example 3
[0160] The specific steps and methods are the same as those in Example 1, except that the vapor phase alloying reaction is carried out at 500° C. for 15 minutes.
[0161] Comparative Example 4
[0162] The specific steps and methods are the same as those in Example 1, except that the reaction temperature of the gas phase alloy reaction is selected from 1000° C. and the reaction time is selected from 60 min.
[0163] Comparative Example 5
[0164] The specific steps and methods are the same as those in Example 1, except that the low vacuum oxidation time of the self-limiting oxidation reaction is selected from 2 hours.
[0165] Electrolyzed water performance test:
[0166] Sample preparation:
[0167] The dried porous nickel mesh electrode material with heterogeneous structure is cut and pretreated as necessary to adapt to the water electrolysis test device.
[0168] Electrolyzed water test:
[0169] The obtained porous nickel mesh electrode material with heterogeneous structure was used as an anode and placed in an alkaline water electrolysis device for testing.
[0170] The tests include hydrogen evolution reaction, electrochemical impedance and double layer tests to evaluate the water electrolysis performance and stability of electrode materials.
[0171] The test equipment includes a CHI-760E electrochemical workstation, an electrode clamp, a Hg / HgO electrode, a carbon rod, and the solution is 1M KOH.
[0172] The electrode material of the electrode clamp is the nickel mesh as the working electrode, the Hg / HgO electrode is the reference electrode, and the carbon rod is the counter electrode.
[0173] Polarization curve test: Polarization curves were recorded by linear sweep voltammetry (LSV) at a potential of -0.4 to 0.1 V vs RHE (reversible hydrogen electrode) with a scan rate of 1 mV s -1 The polarization curve can be used to determine the initial overpotential of the catalyst material (i.e., the additional potential required for the catalyst to initiate hydrogen evolution).
[0174] Tafel plot: This curve is obtained by plotting the overpotential (the difference between the electrode potential and the equilibrium potential) against the logarithm of the current density, usually in the slightly polarized region.
[0175] Electrochemical impedance spectroscopy (EIS) was performed at -0.1 V vs RHE with a frequency of 10 5 Hz to 0.01Hz. The internal resistance Rs and interface charge transfer resistance Rct were obtained by fitting.
[0176] Double layer capacitance (Cdl) test: In the non-Faraday potential region (0-0.1V vs RHE) at 0.2mV s -1 To 2mVs -1 Cyclic voltammetry (CV) tests were performed at different scan rates. Then the current density and scan rate at a certain potential were plotted to obtain a straight line, and the slope of the line was the double layer capacitance.
[0177] Stability test: Generally, there are two methods for stability test: cyclic voltammetry (CV) and constant potential (constant current) method. In cyclic voltammetry test, the catalyst undergoes multiple CV cycles in the reaction potential range. If there is no obvious difference in the starting potential and peak current before and after the reaction, it means that the stability is good. In constant potential (constant current) test, it is necessary to maintain a given voltage or current for several hours without obvious potential or current changes, which means that the stability is good. In this work, the accelerated cyclic voltammetry (CV) test was performed at 50mV s -1The scan rate was maintained at 1000 cycles. The current density was kept at 10 mA cm -2 and 100mA cm -2 The duration is 48h and 200h.
[0178] The test results of Examples 1-5 and Comparative Examples 1-5 are shown in Table 1.
[0179] Table 1
[0180]
[0181]
[0182] It can be seen from the data in Table 1 that the porous nickel mesh electrode material with a heterogeneous structure prepared in the embodiment within the optimization range of the present invention has better hydrogen evolution reaction performance than the nickel mesh electrode material in the comparative example. Only a very small overpotential is required to achieve a high current density, and it has good stability, can be prepared on a large scale, and has the potential to become a commercial alkaline water electrolysis electrode material. The scheme of constructing intermetallic compounds and surface porosity by gas phase alloying mentioned in the present invention also provides a new idea for the preparation of various heterogeneous substrate materials.
[0183] It can be found from the data of Example 1, Example 2, Comparative Examples 1-3, and Table 1 that Example 1 has better hydrogen evolution reaction performance than Comparative Example 1. Figure 1 It can be seen from e that after 1000 accelerated CV tests, the electrode has a high conductivity at 800 mA cm -2 The overpotential under γ is only slightly increased. Figure 1 f, 10 mA cm -2 At low current density, the overpotential of NM / Ni / NiO-30-30d remained basically unchanged. In the 200h chronopotentiometry test, the overpotential increased by only a dozen millivolts. -2 Under the same conditions, the porous nickel mesh electrode material with heterogeneous structure prepared by the present invention also shows excellent stability, and the overpotential is only slightly increased. It can be seen that the porous nickel mesh electrode material with heterogeneous structure of the present invention has high catalytic activity and stability.
[0184] Specifically, the present invention Figure 1 The hydrogen evolution performance of the catalyst obtained in a was tested. Figure 1 From the LSV polarization curve in a, it can be seen that the sample after self-limiting oxidation stabilization is compared with the commercial catalyst at 800 mA cm -2 The overpotential at high current density is better than that of commercial catalysts (η 800 =418mV). Figure 1b shows the difference in double layer capacitance of samples with different alloying degrees after dealloying. The double layer capacitance of NM / Ni / NiO-15min-30days is 3375mF cm -2 , while the double layer capacitance of NM / Ni / NiO-30min-30days and NM / Ni / NiO-60min-30days increased to 5034.5mF cm -2 and 7738.7mF cm -2 . Compared with the commercial catalyst 457mF cm -2 In comparison, the electrochemical active area of the catalyst electrode prepared by the present invention is greatly improved, and the increase in the number of corresponding active sites brings about an improvement in HER catalytic activity. Figure 1 The Tafel slope of NM / Ni / NiO-30-30d in the Tafel curve of c is 91.1 mV dec -1 , showing a rate-determining step for hydrogen evolution in water electrolysis under acidic conditions. In contrast, the Tafel slopes of NM / Ni / NiO-15-30d and NM / Ni / NiO-60-30d are not much different from that of NM / Ni / NiO-15-30d, proving that the surface reaction kinetics of the electrodes prepared under the alloying and then dealloying strategy are similar. Figure 1 d The HER charge transfer resistance (Rct) measured by EIS impedance spectrum found that at an overpotential of 100 mV, the Rct of the untreated original nickel mesh was 481 Ω, while that of the NM / Ni / NiO-30-30d treated in this work was reduced to 4.7 Ω. Low Tafel slope, low Rct and small overpotential (η 100 =103mV,η 800 =237mV), which together demonstrates the fast HER kinetics and high catalytic efficiency of the NM / Ni / NiO-30-30d catalyst electrode in the hydrogen evolution reaction of alkaline water electrolysis. Figure 1 e, After 1000 cycles of accelerated CV test, the electrode -2 The overpotential under the condition of 237mV increased to 276mV. Figure 1 f, 10 mA cm -2 At low current density, the overpotential of NM / Ni / NiO-30-30d remained basically unchanged. In the 200h chronopotentiometry test, the overpotential increased from 54mV to 70mV. -2 Under these conditions, the catalyst also exhibited excellent stability, with only a slight increase in overpotential from 130 mV to 143 mV.
[0185] In addition, through Figure 2It can be seen that the preparation process of NM / Ni / NiO electrode material is that the nickel mesh is alloyed with the zinc surface by vapor phase alloying (VPA) at 500°C to generate a nano nickel-zinc alloy layer on the surface of the nickel mesh; the alloy layer includes Ni 2 Zn 11 Layer, NiZn y layer; then 1M (NH 4 ) 2 SO 4 The aqueous solution is used as the dealloying medium to remove the surface Ni 2 Zn 11 The layer dealloying was performed to obtain a nano-nickel mesh material (NM / Ni) with a double continuous pore structure. Finally, in order to avoid the risk of spontaneous combustion of highly active nanoporous nickel exposed to air, the freshly prepared nanoporous nickel was dried by self-limiting oxidation reaction in a thin air environment. This controlled environment is conducive to the gradual oxidation of the NM / Ni surface, thereby forming a thin NiO layer in situ on the double continuous pore surface, thereby forming a Ni / NiO heterostructure and obtaining a NM / Ni / NiO catalyst electrode.
[0186] In the present invention Figure 3 a XRD results show that under the three alloying time conditions, the products of gas phase alloying are all Ni 2 Zn 11 Intermetallic compounds and a small amount of NiZn intermetallic compounds. After chemical dealloying, Ni 2 Zn 11 The Zn is removed to form nanoporous nickel (NM / Ni) with a bicontinuous porous structure layer, while the NiZn phase does not change. Figure 3 (bd) Further analysis of the cross section by SEM test shows that the diameters from the surface to the inside are 9.8μm, 15.3μm and 38.9μm, respectively. EDS analysis of the sample shows that the alloyed material is Ni from the outside to the inside. 2 Zn 11 , NiZn, Ni substrate material. The NiZn layer, as an incompletely alloyed intermediate product, connects the porous nickel and the nickel mesh skeleton, increasing its connection strength. Figure 3The mechanical properties test results of f, comparing the stress-strain curves of different nickel meshes in the figure, show that the elongation at break of the original nickel mesh is 22.6%, while the elongation at break of the nickel mesh after vapor phase alloying and dealloying is reduced. This is because the macroscopic mechanical properties of the surface porous layer are very poor, resulting in a reduction in the cross-sectional area of the actual stress-bearing inner layer nickel substrate, which makes the mechanical properties worse. However, by comparing the difference in stress at the breaking point, it is found that the NM / Ni / NiO-15min after 15min vapor phase alloying treatment is not much different from the original nickel mesh, which is 82MPa and 77MPa, while the samples after alloying for 30min and 60min show a certain degree of reduction. And for electrode materials, conductivity is very important. The conductivity of different treatment conditions and original nickel mesh and commercial catalysts was compared using a four-probe test system, and it was found that their performance differences were not much different. NM / Ni / NiO-15min, NM / Ni / NiO-30min, NM / Ni / NiO-60 and NM were 4348S / cm, 5000S / cm, 4545S / cm and 3846S / cm respectively; while the commercial catalyst was slightly better at 6667S / cm. Compared with the balance of mechanical properties and conductivity and the number of active sites of nanoporous nickel (alloy layer thickness), the best physical properties were shown when the nickel mesh material was subjected to a vapor phase alloying reaction of zinc for 30 minutes.
[0187] In the present invention Figure 4 The surface composition and valence distribution of the electrode material in a were characterized by X-ray photoelectron spectroscopy (XPS). Figure 4 a From the full spectrum data, we can see that the binding energy regions of Ni, Zn and O can be observed in the fully oxidized NM / Ni / NiO-30min. Figure 4 From the Ni 2p spectrum in b, the peaks at 852.9 eV and 869.8 eV come from metallic Ni. In addition, there are two peaks at 856.2 eV and 873.9 eV, corresponding to Ni 2+ The peaks at 1022.2 eV and 1045.3 eV can be assigned to metallic zinc due to the surface oxidation that occurs during dealloying and self-limiting oxidation. Figure 4 c. Figure 4 From the O1s spectrum in d, it can be clearly observed that the peaks at 529.5, 531.8, and 533.3 eV correspond to the metal oxygen bonds (MO), hydroxyl radicals (M-OH), and adsorbed water on the surface of NM / Ni / NiO-30min, respectively.
[0188] In the present invention Figure 5 a It can be seen that compared with the commercial nickel mesh catalyst, the catalyst NM / Ni / NiO material shows better bonding ability with the base nickel mesh both macroscopically and microscopically. The electron microscopy results of the commercial catalyst are shown in Figure 5a It can be seen that its bonding with the nickel mesh is not strong and uneven. This is due to the limitation of its preparation scheme. The hot melt sprayed nickel-aluminum alloy cannot bond with the joint of the woven nickel mesh, resulting in the loss of active sites. Figure 5 c The sample of vapor phase alloying shows that Zn is tightly bonded to the nickel mesh alloy layer, and the thickness is uniform. Further analysis of the commercial catalytic surface shows the difference in the active sites of the surface nanoporous nickel oxide. Figure 5 In b, the commercial catalyst not only has pore coarsening caused by the intense heat release of porous nickel in the air, but also has a NiO layer with tubular ligaments, because direct oxidation in air can lead to spontaneous combustion and over-oxidation. In contrast, the self-limiting oxidation scheme used in the present invention can transform the growth mode of nickel oxide into a well-regulated, self-limited surface oxidation process. The test results of Example 1 show that the average thickness of the oxide layer is 3nm, forming a uniform Ni / NiO heterostructure.
[0189] Similarly, it can be seen from Examples 1-5 and Comparative Examples 2, 3 and 4 that Comparative Examples 2, 3 and 4 all have higher overpotentials and higher Tafel slopes and electrochemical impedances than Examples 1-5; this may be because when preparing porous nickel mesh electrode materials with heterogeneous structures in Comparative Examples 2, 3 and 4, the selected preparation parameters are not within the preferred range of the present invention. In Comparative Example 4, when the selected gas phase alloying reaction temperature is too high, it is easy to cause excessive volatilization of zinc, resulting in complete alloying of the nickel framework. The electrode structure formed after dealloying and self-limiting oxidation is very unstable and has poor electronic conductivity. It has poor stability in the process of electrolyzing water to produce hydrogen as a catalytic electrode, and exhibits high electrochemical impedance and overpotential.
[0190] In Comparative Example 5, when low-vacuum oxidation of a self-limiting oxidation reaction is carried out, the selected low-vacuum oxidation time is too short to form a uniform and dense oxide layer. The material is prone to local spontaneous combustion when placed in the air, resulting in uneven distribution of active sites on the electrode surface, causing a high overpotential for electrolysis of water, hindered reaction kinetics, a large Tafel slope, and reduced catalytic performance.
[0191] In summary, the nickel mesh-loaded nanoporous nickel electrode developed by the present invention based on the in-situ construction technology of the nanoporous structure has good stability in the air and better catalytic efficiency.
[0192] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous nickel mesh electrode material with a heterogeneous structure; comprising the following steps: S1: Zinc and nickel mesh are subjected to a vapor phase alloying reaction to generate a nano nickel-zinc alloy layer on the surface of the nickel mesh; the alloy layer includes Ni2Zn 11 Layer, NiZn y Layer; NiZn y The layer is an incompletely alloyed nickel-zinc transition layer; the NiZn y wherein the range of y is selected from Ni:Zn=1:(1-4); S2: subjecting the nickel mesh material containing the nano nickel-zinc alloy layer described in S1 to chemical dealloying treatment with an ammonium sulfate solution to obtain a nano nickel mesh material having a double continuous porous structure layer on the surface; S3: subjecting the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2 to a self-limiting oxidation reaction to obtain a porous nickel mesh electrode material having a nano nickel / nickel oxide heterostructure on the inner surface of the pore structure of the double continuous porous structure layer.
2. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The NiZn y The range of y is selected from Ni:Zn=1:1; the NiZn contained in S1 y Layer thickness and Ni2Zn 11 The layer thickness ratio ranges from 1:(5-8).
3. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The treatment temperature of the gas phase alloying reaction in S1 is selected from 300-700°C; the treatment time is selected from 0.5-4h; and the vacuum pressure is selected from 10-50Pa; Furthermore, the processing temperature of the gas phase alloying reaction in S1 is preferably from 450 to 600°C.
4. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The mass of zinc in S1 is 10-100 times the mass of nickel mesh; the time of chemical dealloying in S2 is selected from 8-16h, and the temperature is selected from 40-60°C; the molar concentration of ammonium sulfate solution in S2 is selected from 0.5-2.5M; Furthermore, the molar concentration of the ammonium sulfate solution in S2 is preferably 1M.
5. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The step of the self-limiting oxidation reaction comprises vacuum drying the nano nickel mesh material having a double continuous porous structure layer on the surface described in S2, and then performing low vacuum oxidation; Further, the vacuum drying temperature is selected from 20-30°C, and the vacuum drying time is selected from 3-24h; Furthermore, the vacuum degree of the low vacuum oxidation is in the range of 1×10 -5 -1×10 3 Pa, the temperature of low vacuum oxidation is selected from 20-30°C, and the time of low vacuum oxidation is selected from 12-48h; Furthermore, the vacuum drying time is preferably 3-5 hours; Furthermore, the low vacuum oxidation time is preferably from 24 to 36 hours.
6. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The step S31 is further followed by step S32: exposing the prepared porous nickel mesh electrode material having a nano-nickel / nickel oxide heterostructure to an air environment for 7-30 days for continuous oxidation.
7. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: The step S11 is preceded by the step S1, wherein the step S11 comprises subjecting the nickel mesh to two sequential pretreatments; the first pretreatment is washing the nickel mesh with a solvent; the second pretreatment comprises treating the nickel mesh after the first pretreatment in an acid solution, and then washing and drying the nickel mesh with a pure water solution; The step S11 further comprises treating the zinc in an acid solution, and then washing and drying the zinc in a pure water solution; Furthermore, in S11, the solvent used in the first pretreatment is selected from one or more solvents of acetone, methanol, ethanol, petroleum ether, ethyl acetate, and ethylene dichloride; Furthermore, in S11, the washing treatment includes using ultrasound for treatment; the ultrasound time is selected from 10-30 minutes; the ultrasound temperature is selected from 20-30° C.; the number of ultrasounds is selected from 2-5 times; Further, in S11, the acid solution is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, and acetic acid; wherein the molar concentration of the hydrochloric acid is selected from 2-4M; the concentration of the sulfuric acid is selected from 0.1-1M; the concentration of the nitric acid is selected from 3-5M; the molar concentration of the acetic acid is selected from 2-5M; Furthermore, the drying method is preferably air-drying at room temperature.
8. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1, characterized in that: There is also a step S21 between S2 and S3; the step S21 comprises washing the nano nickel mesh material having a double continuous porous structure layer on the surface obtained in S2 with water and ethanol in sequence.
9. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 1; characterized in that: The device used for the gas phase alloying reaction in S1 includes the following components: A heating device (1) for providing a temperature required for a gas phase alloying reaction; A quartz tube (2) used in conjunction with the heating device (1) is used to contain the nickel mesh (9) and the zinc (10), provide a gas phase alloying reaction space and maintain a vacuum environment; A temperature sensor (3); the temperature sensor (3) is arranged between the quartz tube (2) and the heating device (1) and is used to monitor and control the required temperature of the quartz tube (2); A vacuum pump (4) connected to one side of the quartz tube (2) and used to maintain a vacuum environment inside the quartz tube (2); A vacuum gauge (5) is connected between the vacuum pump (4) and the quartz tube (2) and is used to monitor and regulate the vacuum pressure required by the quartz tube (2); A graphite boat (7) with a cover, wherein the graphite boat (7) with a cover is a cylindrical structure with a hollow interior, is accommodated inside the quartz tube (2), and is used to place the nickel mesh (9) and the zinc (10); the zinc (10) is evenly distributed on the bottom of the inner wall of one side of the graphite boat (7) with a cover; A plurality of support members (11) are sequentially arranged in the covered graphite boat (7) along the length direction of the covered graphite boat (7), wherein the support members (11) are arranged at intervals at the bottom of the inner wall of one side of the covered graphite boat (7) and are used to support the nickel mesh (9) to prevent the nickel mesh (9) from contacting the zinc (10).
10. The method for preparing a porous nickel mesh electrode material with a heterogeneous structure according to claim 9; characterized in that: The device further comprises a graphite tube (6), wherein the graphite tube (6) is an internal hollow structure and is placed inside the quartz tube (2), and the inside of the graphite tube (6) is used to accommodate a graphite boat (7) with a cover; Furthermore, both ends of the graphite tube (6) are provided with detachable graphite plugs (8); Furthermore, the support member (11) is selected from one or more high temperature resistant materials such as ceramic rods and quartz rods; Furthermore, the spacing distance of the support members (11) is selected from one half to one quarter of the length of the graphite boat with cover (7), so that the inside of the graphite boat with cover (7) is equally divided and can support the nickel mesh (9); Furthermore, the covered graphite boat (7) is greater than 1 meter away from the outlet of the graphite tube (6).